Dynamic efficiency and reswitching - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2008)
The paper argues that, from a dynamic efficiency perspective, intersections of factor price frontiers are irrelevant to the choice of techniques. Because every change in technique involves a temporary loss or gain in both profit and per capita consumption within the transition period, its profitability should be calculated by applying the present value criterion to the entire change process. With only one transition period, there is generally a unique interest rate at which the change in technique breaks even. This critical interest rate is generally the same for a profit maximizing firm as for a central planner who seeks to maximize consumption per unit of work. This critical interest rate does not generally coincide with either of the interest rates at which the factor price frontiers intersect. Therefore, common proofs of the socalled reswitching phenomenon do not stand up well from a dynamic efficiency perspective.
Keywords: B16; B5; D2; D5; D9; E1; E4; 330